Examining the challenges of simulating surface water–groundwater interactions in a post-glacial environment. Issue 2 (3rd April 2018) - Turgeon, Félix; Larocque, Marie; Meyzonnat, Guillaume; Dorner, Sarah; Bourgault, Marc-André
Abstract : Although integrated models are increasingly used for water management purposes, detailed applications of these models under different conditions are necessary to guide their implementation. The objective of this study was to examine some of the challenges encountered when simulating surface water–groundwater interactions in a post-glacial geological environment. The integrated Mike SHE model was used to simulate transient-state heads and flows in the Raquette River watershed in the Vaudreuil-Soulanges region of southwestern Quebec (Canada) over a 2-year period. This application benefited from a detailed hydrogeological database recently developed for the region. Overall, flows, heads and groundwater inputs to the river were adequately simulated. A sensitivity analysis has shown that many hydrogeologic and surface flow parameters have an impact on both flow rates and heads, thus underlining the importance of using an integrated model to study watershed-scale water issues. Additional flow rate measurements to improve the quality of rating curves and continuous flow measurements in tributaries could improve model calibration. An explicit simulation of unsaturated zone infiltration processes, including soil flow, plant and evaporation processes, as well as the inclusion of the agricultural tile drainage system, could reduce simulation errors. Extending the model calibration over a longer period, including contrasting hydrological conditions, would make the model more robust in view of its use for water management under land use and climate change conditions. Nevertheless, this work demonstrated that, using data readily available for southern Québec aquifers, it is possible to build an integrated model that is representative of actual hydrological conditions. The maintenance and improvement of this model for long-term use is recommended.